2018
DOI: 10.1111/mec.14897
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of genetic adaptation to extremely varied Australian environments in introduced European house sparrows

Abstract: Due to its history of multiple introductions to novel environments worldwide, the house sparrow has been used as a model species to study local adaption in invasive avian species. New genomic resources such as a custom 200K SNP array and a house sparrow reference genome provide great prospects for studying rapid local adaptation in this invasive species. Here, we analyse high-density genomewide genetic data collected across an extensive range of temperate, arid and tropical climates, in Australian populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 81 publications
(112 reference statements)
2
13
0
Order By: Relevance
“…(2013) to select candidate SNPs using a consensus approach, allowing for robust identification of adaptive loci independent from assumptions (and limitations) of a single model (Rellstab et al., 2015). In our study, numbers of loci identified with signals of selection varied by species, climatic variable and method; this has also been observed in other genomics studies (e.g., Ahrens, Byrne, & Rymer, 2019; Andrew, Jensen, Hagen, Lundregan, & Griffith, 2018; Hopley & Byrne, 2019). Furthermore, the overall proportion of SNPs identified as putatively adaptive in this study were similar to those observed in plant (e.g., Ahrens et al., 2019; Hopley & Byrne, 2019; Shryock et al., 2017) and other landscape genomic studies (e.g., Dudaniec, Yong, Lancaster, Svensson, & Hansson, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…(2013) to select candidate SNPs using a consensus approach, allowing for robust identification of adaptive loci independent from assumptions (and limitations) of a single model (Rellstab et al., 2015). In our study, numbers of loci identified with signals of selection varied by species, climatic variable and method; this has also been observed in other genomics studies (e.g., Ahrens, Byrne, & Rymer, 2019; Andrew, Jensen, Hagen, Lundregan, & Griffith, 2018; Hopley & Byrne, 2019). Furthermore, the overall proportion of SNPs identified as putatively adaptive in this study were similar to those observed in plant (e.g., Ahrens et al., 2019; Hopley & Byrne, 2019; Shryock et al., 2017) and other landscape genomic studies (e.g., Dudaniec, Yong, Lancaster, Svensson, & Hansson, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…Given the unique advantages and disadvantages of each approach, unique combinations of PD and EA may help to reduce the number of false negatives and promote uncovering potential genomic footprints of selection [ 20 ]. For example, both PD and EA methods have been employed for the successful detection of putatively adaptive loci and assessment of environmental parameter influence on genetic variation within and among populations [ 7 , 10 , 20 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The house sparrow ( Passer domesticus ) is a ubiquitous passerine bird that has been used as an ecological model species in previous genetic architecture studies (Andrew, Jensen, Hagen, Lundregan, & Griffith, 2018; Andrew et al., 2019; Lundregan et al., 2018; Silva et al., 2017). In Helgeland, northern Norway, a natural metapopulation of house sparrows has been studied at an individual level since 1993 and has a large sample archive with records of morphological and life history data, alongside individual genetic and pedigree information (Jensen et al., 2003, 2004; Pärn, Jensen, Ringsby, & Sæther, 2009).…”
Section: Introductionmentioning
confidence: 99%